Native bee pollinators and pollen sources of Apidae (Hymenoptera) in four forest types of Lower northern Thailand - Jongjitvimol, Touchkanin; Petchsri, Sahanat (Universiti Kebangsaan Malaysia, 2015)
Bee species diversity and pollen sources of Apidae (Hymenoptera) in Thung Salaeng Luang National Park, lower northern Thailand, were studied from 2011 to 2012. The forest types encountered were deciduous dipterocarp, deciduous with bamboo, seasonal evergreen and dipterocarp - pine forests. Sweep nets and honey bait traps were used to collect bee samples. The beta diversity of native bees was high with 22 recorded insect species from 12 genera and pollen grains collected by native bees were 62 plant species from 28 families. The plant family Fabaceae (Leguminosae) contained the greatest number of species (9 species). The main pollen source of native bees was Hopea odorata Roxb. (Dipterocarpaceae) which was collected by 19 bee species. The result from biodiversity indices i.e. species diversity (H’), species evenness (J’), similarity habitat (Ss ) and species richness (D) indicated that this area has relatively high species diversity. In addition, the dwarf honey bees, Apis florea Fabricius, 1787, are the main pollinator at the study site with the highest number of pollinated plant species (46 species). Thus, this bee could be used as a biological indicator for future studies.